UWB printed antenna for medical applications - Shanwar A.R.; Othman N.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bandwidth; Computer software; Frequency bands; Medical applications; Microstrip antennas; Slot antennas; Broad bandwidths; Computer simulation technology; Computer simulation technology (CST); Frequency ranges; Lower frequencies; Medical fields; Micro-strip patch antennas; Radiation efficiency; Ultra-wideband (UWB)